Spodbujanje družinskega branja v otrokovem predšolskem obdobju: Predšolska bralna značka - Haramija, Dragica (Slavia Centralis, 2020)
Encouraging Family Literacy in Child’s Pre-school period: the Pre-school Reading Badge The paper focuses on the development of family literacy (family reading), which is one of the foundations of the Pre-school Reading Badge (Predšolska bralna značka, PBZ). With the help of the survey, we obtained relevant information on the involvement of children in PBZ and descriptions of certain other activities that promote family reading. We were also interested in the work of reading mentors, especially in the ways of choosing the recommended materials for reading in the family and in the methods of verifying the material read. The concluding part of the paper provides guidelines for the preparation of quality reading lists with the goal of helping parents and children to select proper reading materials. Promoting family reading is one of the objectives of the National Strategy for the Development of Reading Literacy (2017), which carefully assesses the specific goals and levels of literacy from children in pre-school age to adults.